En Bloc Resection in Peritoneal Carcinomatosis with Hyperthermic Intraperitoneal Chemotherapy (HIPEC) in Appendiceal Cancer: Surgical Strategies, Oncologic Outcomes, and Epidemiological Insights - Luis Jorge Caldera Sanchez; Héctor Cisneros Pérez; Mario Hernandez Mancillas; Víctor Mario Ortega Valerio; Francisco Rico Fernández; Marina Gallegos Colón (International Journal of Medical Science and Clinical Research Studies, 2025)
Appendiceal cancer with peritoneal carcinomatosis (PC) represents a complex oncologic condition with distinct biological behavior and therapeutic challenges. Unlike other gastrointestinal malignancies, appendiceal neoplasms often exhibit extensive peritoneal dissemination, particularly in mucinous subtypes such as low-grade appendiceal mucinous neoplasms (LAMN) and pseudomyxoma peritonei (PMP). Historically, peritoneal dissemination was associated with poor prognosis, but the advent of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) has dramatically altered the disease trajectory. En bloc resection has emerged as a critical surgical strategy to achieve complete cytoreduction (CC-0/1) in cases with extensive peritoneal involvement, preventing tumor fragmentation and reducing recurrence risk. Epidemiologically, appendiceal neoplasms are rare, with an incidence of approximately 0.12 cases per 100,000 individuals per year, accounting for less than 1% of all gastrointestinal malignancies. Despite their low incidence, the diagnosis of appendiceal cancer has been increasing due to advancements in imaging modalities and more frequent incidental discoveries during appendectomies. The prognosis of appendiceal cancer varies widely depending on histologic subtype, peritoneal carcinomatosis index (PCI), and the feasibility of complete cytoreduction. This article explores the epidemiology, surgical principles, and oncologic outcomes of en bloc resection in conjunction with HIPEC, emphasizing patient selection criteria, operative techniques, and perioperative management. Additionally, we analyze the impact of histopathological subtypes on treatment response, recurrence patterns, and survival outcomes, providing a comprehensive overview of this aggressive but potentially curative approach to managing peritoneal carcinomatosis from appendiceal malignancies.